Business language evolution – accounting - Lew, Grzegorz (Współczesne Problemy Zarządzania, 2019)
All decisions of entrepreneurs and actions are determined by economic accounts. Each action has financial implications. Entrepreneurs looking for the possibility to record the financial consequences of their decisions naturally created an accounting system, which has become a widespread and universal information system of companies all over the world. Accounting has also changed with the development of companies on global markets. This evolution has led to the separation of two main accounting subsystems: financial and management accounting. Analyzing the process of accounting evolution, it can be concluded that the subsequent stages cover a shorter and shorter period of time, which can be interpreted as a constant acceleration of changes in accounting and consequently in the development of markets and companies in the global market. The main research method used to write the paper was a critical review of literature and desk research.